Soil legacies in maize-edible legume intercropping alter maize growth and reduce Spodoptera frugiperda larval feeding - Jalloh, Abdul A.; Yusuf, Abdullahi Ahmed; Khamis, Fathiya; Subramanian, Sevgan; Mutyambai, Daniel Munyao (Frontiers in Agronomy, 2023)
Plant-soil feedback can influence aboveground interactions between plants and herbivores by affecting plant chemistry. Such interactions can be utilized in pest management. However, cropping systems such as maize-legume intercropping (MLI) can influence these interactions which is not well understood. In this study, we explored effects of MLI systems on soil physico-chemical properties, maize growth, larval feeding and development of fall armyworm (Spodoptera frugiperda). We used sterile soil and soil conditioned by different MLI and maizemonoculture cropping systems to explore these interactions. Soil samples that included soil conditioned by different MLI and maize-monoculture cropping systems were collected from smallholder farmer fields in eastern Kenya, where different MLI and maize-monoculture cropping systems were being practiced. These soil samples were compared with sterile soils for physico-chemical properties using black oxidation and Walkley methods. Three-weeks-old maize plants grown in the different soil treatments in the greenhouse were used for larval feeding and development assays. Neonate S. frugiperda larvae were allowed to feed on maize leaf discs for 24 hours and another set of plants were inoculated with the neonates for 15 days and the larval survival and development monitored. Soil obtained from different maize-edible legume intercropping systems had a higher pH, electrical conductivity, nitrogen, organic carbon, potassium, phosphorus, calcium, magnesium, exchangeable acidity, copper, clay and silt compared to maize monoculture and sterile soil. Maize plants grown in MLI soil had better growth parameters compared to those in maize-monoculture and sterile soils. A high correlation was found between pH and plant biomass, while no significant correlation with other physico-chemical properties was noted. There were significant differences in larval feeding by S. frugiperda neonates when exposed to constitutive and induced maize leaf discs with more leaf tissue fed on maize grown in maize-monoculture and sterile soil. When allowed to feed for 15 days, S. frugiperda larval weight and length were significantly lower on maize plants grown in soils conditioned by MLI than those grown in soil conditioned by maizemonoculture and sterile soils. Findings from this study show how conditioning soil by MLI systems improve soil health, maize growth and reduces S. spodoptera larval feeding and development.